A novel mathematical model to estimate the ride frequency of an off road vehicle with experimental validation. (2021) - Mittal, Ankit; Misra, Ashwin
Abstract: Off-road suspension design is plagued with many practical design problems including the lack of availability of accurate terrain profiles and the lack of a proper methodology to determine suspension parameters such as ride frequency. The existing methodologies for obtaining road profiles are out dated and give inaccurate and impractical results. This article aims at obtaining a sophisticated and accurate methodology through concepts of mathematical modeling and Vehicle Dynamics for determining the suspension setup for an off-road vehicle with experimental validation through real-time sensor data. A particular type of All-Terrain Vehicle (ATV) – The Baja SAE Vehicle forms the main basis for this article.